Vagus Nerve Stimulation: A Potential Adjunct Therapy for COVID-19 - Azabou, Eric; Bao, Guillaume; Bounab, Rania; Heming, Nicholas; Annane, Djillali (Frontiers in Medicine, 2021)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19) through excessive end organ inflammation. Despite improved understanding of the pathophysiology, management and the great efforts worldwide to produce effective drugs, death rates of COVID-19 patients remain unacceptably high and effective treatment is unfortunately lacking. Pharmacological strategies aimed at modulating inflammation in COVID-19 are being evaluated worldwide. Several drug therapies targeting this excessive inflammation, such as tocilizumab, an IL-6 inhibitor, corticosteroids, programmed cell death protein (PD)-1/PD-L1 checkpoint inhibition, cytokine-adsorption devices and intravenous immunoglobulin have been identified as potentially useful and reliable approaches to counteract the cytokine storm. However, little attention is currently payed for non-drug therapeutic strategies targeting inflammatory and immunological processes which may be useful for reducing COVID-19 induced complications and improving patient outcome. Vagus nerve stimulation attenuates inflammation both in experimental models and preliminary data in human. Modulating the activity of cholinergic anti-inflammatory pathways (CAP) described by the group of KJ Tracey has indeed become an important target of therapeutic research strategies for inflammatory diseases and sepsis. Non-invasive trans-cutaneous vagal nerve stimulation (t-VNS), as a non-pharmacological adjuvant may help reduce the burden of COVID-19 and deserve to be investigated. VNS as an adjunct therapy in COVID-19 patients should be investigated in clinical trials. Two clinical trials on this topic are currently underway (NCT04382391 and NCT04368156). The results of these trials will be informative but additional, larger, studies are needed.